2015
DOI: 10.1097/qmh.0000000000000069
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated With Reintubation in Patients With Chronic Obstructive Pulmonary Disease

Abstract: Sedative and analgesic drug use prior to extubation was associated with more frequent reintubation in patients with acute exacerbations of COPD. This study suggests that the judicious withdrawal of sedatives prior to extubation may reduce reintubations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 39 publications
2
13
0
Order By: Relevance
“…Based on the findings described herein, an unplanned extubation risk assessment tool should consider the presence of delirium, agitation, mode of mechanical ventilation, and time of day (e.g., night/day shifts) as risk factors for unplanned extubation in the ICU [17]. To ensure high quality of care and improve the safety of patients and staff in the ICU, these factors should be assessed by evaluating their working systems.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the findings described herein, an unplanned extubation risk assessment tool should consider the presence of delirium, agitation, mode of mechanical ventilation, and time of day (e.g., night/day shifts) as risk factors for unplanned extubation in the ICU [17]. To ensure high quality of care and improve the safety of patients and staff in the ICU, these factors should be assessed by evaluating their working systems.…”
Section: Discussionmentioning
confidence: 99%
“…Cough strength is strongly associated with re-intubation; patients with a weak cough are more likely to expe-rience re-intubation. 5,[9][10][11][12][13][14][15][16][17][18][19][20] Cough peak flow (CPF) is commonly used to reflect cough strength because it is an objective measurement. A flow meter is the most common device to measure CPF.…”
Section: Introductionmentioning
confidence: 99%
“…However, not all ICUs provide a flow meter to measure CPF; some of them use a semiquantitative cough strength assessment. 5,[9][10][11][12][13] However, a semiquantitative assessment is not as accurate as an objective assessment. Thus, a device existing in all ICUs serving as an objective measurement of cough strength is needed.…”
Section: Introductionmentioning
confidence: 99%
“…In another study, it has been reported that COPD patients needing aspiration at 2-hours or shorter intervals have a 16-fold increased risk of re-intubation. Therefore, the quantitative measurement or subjective grading of the amount of secretions before extubation in COPD patients is used for predicting successful extubation (25)(26)(27).…”
Section: Chronic Obstructive Pulmonary Disease (Copd)mentioning
confidence: 99%